(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The objective is to prepare extended release micro-pellets of the s-Metoprolol Succinate which is chirally pure molecules. Commercially Metoprolol Succinate is available the racemic mixture of the s and r isomers. Out of both the isomers s-isomer is predominantly responsible for the cardiac beta blocking activity. So to use the more desirable beta blocking activity of s-Metoprolol Succinate, extended release micro-pellets of the s-Metoprolol Succinate was prepared. Due to pure chiral molecules the dose was also reduced to half to that of the racemic mixture. Extended release micro-pellets of the s-Metoprolol Succinate was prepared by the fluid bed technology, in which s-Metoprolol Succinate along with binder and anti-adherent material was sprayed on the inert core. These drug loaded pellets of the s-Metoprolol Succinate was than coated with ethyl cellulose as extended release polymer, hypromellose as pore former and acetyl tri butyl as novel plasticizer and talc as an anti-adherent. The formulation was further optimized for drug release, as per USP recommended dissolution condition, using central composite design (CC). Results shows that at level of 58-66% w/w extended release coating with any studied concentration of acetyl tri butyl citrate and hypromellose gives desired drug release profile.